2017
DOI: 10.1111/evj.12710
|View full text |Cite
|
Sign up to set email alerts
|

Histological assessment of β‐amyloid precursor protein immunolabelled rectal biopsies aids diagnosis of equine grass sickness

Abstract: Histological assessment of β-APP immunolabelled rectal biopsies is more sensitive than conventional histological examination in EGS diagnosis. Further validation is required before this technique can be advocated for use in clinical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
0
10
2
Order By: Relevance
“…Beta‐amyloid precursor protein increases in the perikarya of CCG neurons in acute and subacute ED and is thought to be involved in the pathogenesis of ED . The increase in BAPP staining is also of value in the antemortem diagnosis of acute and subacute ED, and there is increased expression in rectal biopsies from ED‐affected horses . In contrast, we found no evidence of significantly greater BAPP staining at any site in the ED cases compared with controls; therefore, accumulation of BAPP does not appear to be a feature of recovered ED cases.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Beta‐amyloid precursor protein increases in the perikarya of CCG neurons in acute and subacute ED and is thought to be involved in the pathogenesis of ED . The increase in BAPP staining is also of value in the antemortem diagnosis of acute and subacute ED, and there is increased expression in rectal biopsies from ED‐affected horses . In contrast, we found no evidence of significantly greater BAPP staining at any site in the ED cases compared with controls; therefore, accumulation of BAPP does not appear to be a feature of recovered ED cases.…”
Section: Discussioncontrasting
confidence: 58%
“…All sections were counterstained with hematoxylin. The immunohistochemistry (IHC) methods have been previously validated for equine tissues in our laboratory …”
Section: Methodsmentioning
confidence: 99%
“…In this study Rachel Jago and colleagues in the UK assessed β‐amyloid precursor protein (β‐APP) immunolabelled rectal biopsies as an aid for diagnosis of equine grass sickness .…”
Section: Equine Grass Sickness Diagnosismentioning
confidence: 99%
“…Rachel Jago from the Royal (Dick) School of Veterinary Studies and Roslin institute of Edinburgh, showed that ß‐amyloid precursor protein (ß‐APP) immunoreactivity was increased in neuronal perikarya and axons in sections of cranial cervical ganglia, ileum and rectum from EGS horses compared with controls. Dr Jago developed a promising antemortem diagnostic test for EGS based on histological assessment of immunolabelled ß‐APP on rectal biopsies . Furthermore, a cross‐sectional study of chronic cases of EGS (cEGS) based on postal questionnaires reported that the most prevalent signs observed by owners were muscle fasciculations, hyperhidrosis and inappetance/anorexia.…”
Section: General Medicinementioning
confidence: 99%